2019
DOI: 10.1002/jhet.3689
|View full text |Cite
|
Sign up to set email alerts
|

Isatin‐1,2,3‐triazole‐isatin Scaffolds and Their Antibacterial Activity

Abstract: Twelve novel isatin‐1,2,3‐triazole‐isatin scaffolds 5a–l were designed, synthesized, and assessed for their in vitro antibacterial activity in this paper. The preliminary results showed that all dimers only endowed with weak antibacterial activity, which was less active than the reference ciprofloxacin. However, the structure–activity relationship was enriched, which may be useful for the further development of more efficient candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Cheng et al [78] . successfully fabricated a novel library of isatin‐1,2,3‐triazole linked isatin hybrids which demonstrated antibacterial activity with reference CPFX (ciprofloxacin) against various clinically important bacteria by twofold agar dilution method.…”
Section: Biological Assessment Of 123‐triazole Tethered Isatin Hybridsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng et al [78] . successfully fabricated a novel library of isatin‐1,2,3‐triazole linked isatin hybrids which demonstrated antibacterial activity with reference CPFX (ciprofloxacin) against various clinically important bacteria by twofold agar dilution method.…”
Section: Biological Assessment Of 123‐triazole Tethered Isatin Hybridsmentioning
confidence: 99%
“…(Reproduced from ref. [78] Copyright (2019), with permission from Elsevier) respectively, as compared to the standard drug fluconazole. Hybrids 145 and 146 synthesized using isatin-linked alkyne 142 and different aryl azides 143 and 144 in one pot using a CuAAC reaction (Scheme 46).…”
Section: Miscellaneous Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of the 1,2,3‐triazole fragment between the two isatin moieties could not enhance the antibacterial activity of isatin dimers as evidenced by the fact that dimers 2 (Figure 2; MIC: 64 to >256 μg/ml) also exhibited weak to moderate activity against 14 Gram‐positive and ‐negative bacteria, and the activity was far less potent than that of ciprofloxacin (MIC: 0.25–32 μg/ml). [ 27 ] Further study suggested that the introduction of neither the electron‐withdrawing nor ‐donating group into C‐5 position (R 1 ) of the isatin skeleton could improve the activity, and replacement of ketone at the C‐3 position (R 2 ) by imine led to the loss of activity. In particular, dimer 2a (MIC: 128 μg/ml) showed the highest activity against MSSE, MRSE, MSSA, and MRSA strains, and it could act as a lead molecule for further modification.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Dimitrakellis [20] et al pointed out that a low surface energy antifouling coating with new nano−antibacterial filler can achieve the effect of antibiological attachment and the dual development of an "active" antibacterial. In previous studies, the triazole ring structure widely used in biopharmaceutics can destroy the biomass membrane [21][22][23][24][25][26][27], which is usually combined with fluorine to achieve a synergistic antibacterial mechanism. The fluorine's strong electronegativity and hydrogen−like mimic effect [28][29][30][31][32] harm bacterial reproduction and growth.…”
Section: Introductionmentioning
confidence: 99%